L'eco di un fantasma (2017) by Azio Corghi A Preliminary Essay (Itinera, 2020)
L’eco di un fantasma (2017) by Azio Corghi went on stage at Teatro Lirico in Cagliari on November 3, 2018. It is a “lyric tragedy” on text by Maddalena Mazzocut-Mis and the subject is inspired by Euripides’ Trojans. I will examine the main characteristics of the composition among the concepts of opera and tragedy.